Disarmament 2007 : critical disarmament issues : panel discussions organized by the NGO Committee on Disarmamant, Peace and Security in cooperation with the Office for Disarmament Affairs on 11, 12, 19 April and 19 October 2007. (United Nations, 2008)
The publication consists of the edited transcripts of four discussions that took place at the United Nations Headquarters in April and October 2007, which were organized by the NGO Committee on Disarmament, Peace and Security, in cooperation with the UN Office for Disarmament Affairs. The focal issue of the three of the discussions was the feasibility of verification of a possible fissile material treaty and of the Biological Weapons Conventions. The value of a code of conduct for outer space was the subject of the fourth discussion.--Publisher's description.